1992
DOI: 10.1016/0014-5793(92)80613-l
|View full text |Cite
|
Sign up to set email alerts
|

GTP‐binding proteins in luminal and basolateral membranes from pars convoluta and pars recta of rabbit kidney proximal tubule

Abstract: The GTP-binding proteins on luminal and basolateral membrane vesicles from outer cortex (pars convoluta) and outer medulla (pars recta) of rabbit proximal tubule have b~n examined. The membrane vesicles were highly purified, as ascertained by electron microscopy, by measurements of marker enzymes, and by investigating seganental-specifie transport systems. The [~SJGTP~,S binding to vesicles, and to sodium cholatc-cxtracted proteins from vesicles, indicated that the total content of GTP-binding proteins were eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…It has been reported that activation of Gi protein might be an important target for several hormones and autacoids that antagonize the Gs protein-coupled effects of AVP. Gαi1, Gαi2 and Gαi3 are known to be present in the nephron cells (Buhl et al, 1992). It seems, therefore, very likely that these pertussis toxin-sensitive species constitute underlying desensitization mechanism of ATP-stimulated cAMP reponses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of Gi protein might be an important target for several hormones and autacoids that antagonize the Gs protein-coupled effects of AVP. Gαi1, Gαi2 and Gαi3 are known to be present in the nephron cells (Buhl et al, 1992). It seems, therefore, very likely that these pertussis toxin-sensitive species constitute underlying desensitization mechanism of ATP-stimulated cAMP reponses.…”
Section: Discussionmentioning
confidence: 99%